Public value theory in public healthcare service system: a proposed framework in the University Hospital of China - Jiaxiang, Luo; Puteh, Fadilah; Othman, Sarina (Faculty of Administrative Science and Policy Studies, 2023)
Health is an inevitable requirement for the promotion of human well-rounded development, and it’s the basic condition for social and economic advancement. Global health concerns must be considered to provide effective, safe, high-quality care. Chinese university hospitals are constantly undergoing transformation, exploration, and rivalry in the era of contemporary healthcare reform. Hospitals are dealing with several issues and difficulties as healthcare reform is fully implemented. Performance needs to meet the serious test, health insurance cost is controlled strictly, drug consumption is free of additional cost, and COVID-19 is severely changing the world. To construct an analytical framework for university hospitals in China, this paper uses strategy management and public value theory in management as its primary theoretical tools. It also draws on the mission management, political management, and operational management dimensions of the "triangle model" of government strategic management. Through proposing the strategic triangle framework into governance of university hospitals in China, it provides the referrals for strategic and sustainable development of university hospitals. To ensure that university hospitals do not deviate from their sustainable development goals, it is determined and advised to university hospital managers how to use the triangle of public value to formulate and maintain effective hospital strategies.